Rational Design, Synthesis, and Comprehensive Characterization of Novel 1,4-Pentadien-3-one Derivatives Bearing Oxime Moieties - Burgaz, Emine Vildan; Tanha, Mahya; Kia, Seyed Armin Houshmand (Turkish Chemical Society, 2025)
The purpose of this research is to synthesize a series of novel 1,4-pentadien-3-one oximes and 1,4-pentadien-3-one O-benzoyl oximes. In this work, new 1,4-pentadien-3-one derivatives with oxime moieties are logically designed, synthesized, and thoroughly characterized. Using a multi-step synthetic strategy, a number of 1,4-pentadien-3-one derivatives were created by functionalizing the core structure with oxime functionalities. The structures of the newly synthesized compounds were determined by several spectroscopic methods, including Nuclear Magnetic Resonance Spectroscopy (1H NMR,13C NMR) and Mass Spectroscopy. © 2025, Turkish Chemical Society. All rights reserved.
Keywords: 1,4-pentadien-3-one; Chalcone; Curcumin; Oxime ether; Synthesis